Effect of Permeation Velocity on Flow Behavior and Pressure Drop in Feed Channels of Membranes - Shakaib, M.; R. M., Yunus (2011)
The computational fluid dynamics (CFD) simulations are carried out for the membrane feed channel. The results are obtained with two different conditions defined at the membrane surface: (i) impermeable wall and (ii) permeable surface with specified velocity. From simulations, the cases in which both boundary conditions yield similar results are indicated